Age model for ODP Leg 202 Site 1235 and Site 1234 - Katrin Hättig; Devika Varma; Marcel T J van der Meer; Gert-Jan Reichart; Stefan Schouten (PANGAEA, 2023)
To compare the neighboring cores ODP Leg 202 Site 1235 and Site 1234, ca. 12 km apart from each other, we constructed an age-depth model with the statistical package Bacon (Blaauw & Christeny, 2011). It is based on the published benthic foraminifera radiocarbon measurements from Muratli et al. 2010 and supplemented here with three new benthic foraminifera 14C data for Site 1235 and the Laschamp event at 41.000 years BP based on correlating magnetic susceptibility (Mix et al., 2003). Radiocarbon ages were converted to calendar years using Marine09 data set (Reimer et al., 2009) with the reservoir age correction given by Muratli et al. 2010.